2009
DOI: 10.1111/j.1439-0272.1992.tb02617.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprolactinaemia and hyperserotoninaemia: their relationship to seminal quality

Abstract: Seminal quality and levels of blood serotonin (5-HT) and serum prolactin (PRL) were determined in 60 men attending an infertility service. Subjects were grouped according to normal or abnormal accessory sex gland function.Subjects with normal accessory sex gland function were further subdivided into groups with asthenozoospermia, polyzoospermia, normozoospermia, oligozoospermia, or azoospermia. Blood 5-HT levels were significantly higher in oligozoospermics (1 15.9k23.7 ng ml-I, P<0.05), and asthenozoospermics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 19 publications
1
22
0
1
Order By: Relevance
“…Daily injections of 5-HT precursor (5-hydroxytryptophan (5-HTP)) alter reproductive development and age-dependent body weight gain in mice, accompanied by a low testosterone level and highly reduced sperm counts, motility, and viability (Sethi & Chaturvedi 2009). In addition, studies in humans reported that hyperserotonemia derives in azoospermia (Gonzales et al 1989(Gonzales et al , 1992. Furthermore, in reproductive pathologies such as varicocele, 5-HT blood levels are elevated and it has also been proven that serotoninergic neurotransmission dysfunctions are involved in premature ejaculation (de Jong et al 2006, Chan et al 2008, Motofei 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Daily injections of 5-HT precursor (5-hydroxytryptophan (5-HTP)) alter reproductive development and age-dependent body weight gain in mice, accompanied by a low testosterone level and highly reduced sperm counts, motility, and viability (Sethi & Chaturvedi 2009). In addition, studies in humans reported that hyperserotonemia derives in azoospermia (Gonzales et al 1989(Gonzales et al , 1992. Furthermore, in reproductive pathologies such as varicocele, 5-HT blood levels are elevated and it has also been proven that serotoninergic neurotransmission dysfunctions are involved in premature ejaculation (de Jong et al 2006, Chan et al 2008, Motofei 2008.…”
Section: Introductionmentioning
confidence: 99%
“…In the male reproductive system, serotonin might affect directly sperm maturation since the existence of a local serotonergic system in the rat caput epididymis have been described [10]. However, relatively recent studies have reported that hyperserotoninaemia may relate to certain kinds of male infertility [11,12]. In this regard, several studies have pointed out that selective serotonin reuptake inhibitors, which are commonly prescribed as antidepressants, can impair semen quality and damage sperm DNA integrity [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…5-HT affects testicular blood flow, testicular development, cAMP and testosterone production (Frungieri et al, 1999). In addition, it was reported in human studies that hyper-serotonemia was associated with decreased sperm count and motility (Gonzales, García-Hjarles, & Velasquez, 1992).…”
Section: Discussionmentioning
confidence: 99%